Available energy and amino acid digestibility of yellow dent corn fed to growing pigs - Lyu, Zhiqian (J Anim Sci, 2019)
Two experiments were conducted to determine the DE and ME as well as the apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of CP and AA in corn fed to growing pigs. All corn was yellow dent corn collected from different areas in China. In Exp. 1, 60 crossbred barrows (Duroc × Landrace × Yorkshire; 40.7 ± 3.5 kg BW) were randomly allotted to 1 of 10 diets to determine the DE and ME of corns. Diets were formulated to contain 96.8% of 1 of the 10 corn samples and 3.2% of other microingredients. In Exp. 2, 11 crossbred barrows (Duroc × Landrace × Yorkshire; 30.5 ± 2.3 kg) fitted with a T-cannula at the distal ileum were assigned to a 6 × 11 Youden square design with 6 periods and 11 diets. Diets included a N-free diet based on cornstarch and sucrose and 10 test diets formulated with 96.6% 1 of the 10 corns as the sole source of AA. Chromic oxide (0.3%) was added to each diet as an indigestible marker for calculating the AA digestibility. On a DM basis, the starch, ether extract (EE), CP, NDF, and ADF contents of corns averaged 74.05% (69.98 to 78.59%), 3.83% (2.04 to 4.73%), 9.63% (7.74 to 10.43%), 10.80% (10.27 to 11.46%), and 2.27% (2.03 to 2.57%), respectively. The CV of EE, CP, and ADF was 22.59, 8.22, and 8.21%, respectively. The DE and ME of corns averaged 4,087 and 3,981 kcal/kg, respectively, and ranged from 3,999 to 4,161 kcal/kg and from 3,898 to 4,067 kcal/kg, respectively. The DE and ME values were positively correlated (P < 0.05) with the EE content. Optimal prediction equations of ME were ME = 940.35 + (0.72 × DE) + (21.88 × EE) (R(2) = 0.94) or ME = 1,051.50 + (0.82 × DE) − (282.05 × ash) (R(2) = 0.99). In Exp. 2, significant differences (P < 0.05) were observed in the SID of Arg, His, Phe, Ala, Pro, Cys, and Tyr. The SID of Lys (average 73.79%), Met (average 87.32%), and Thr (average 80.06%) ranged from 61.45 to 78.47%, from 74.09 to 90.91%, and from 79.19 to 85.79%, respectively. The standardized ileal digestible Met was positively correlated (P < 0.01) with the Met and CP contents. The obtained prediction equations were standardized ileal digestible Met = 31.34 + (3.43 × CP) + (116.04 × Met) and standardized ileal digestible Met = 104.92 + (294.71 × Met) − (7.03 × NDF). In conclusion, sources had an effect on the energy values and ileal digestibility of most AA in corn. The ME can be predicted by the DE combined with either the EE or ash content. The AA concentrations and SID of AA in corn varied largely.